2012
DOI: 10.1161/strokeaha.111.627182
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Profiles of 5-Year Ischemic Stroke Survivors by Oxfordshire Stroke Classification and Hemisphere of Lesion

Abstract: Background and Purpose-Although the neuropsychological literature typically examines stroke outcomes by hemisphere of lesion, the medical literature provides classifications more closely linked to circulatory distribution impacted by stroke. This article examined profiles of cognitive function by hemisphere and by Oxfordshire Community Stroke Project stroke classification. Methods-This study included a sample of 315 5-year ischemic stroke survivors. Assessment included tests of verbal memory, visual memory, wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 31 publications
4
38
0
1
Order By: Relevance
“…Nineteen studies compared lacunar with non-lacunar stroke9–29 35 36 (79% of studies, 95% of subjects), three studies30 32 33 compared lacunar stroke with healthy volunteers and two had no control group. Median study size was 170 patients (range 30–3201) and mean age of the patients was 73 years (we were not able to calculate median age).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nineteen studies compared lacunar with non-lacunar stroke9–29 35 36 (79% of studies, 95% of subjects), three studies30 32 33 compared lacunar stroke with healthy volunteers and two had no control group. Median study size was 170 patients (range 30–3201) and mean age of the patients was 73 years (we were not able to calculate median age).…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies9–17 19–25 27 29 30 35 36 reported the number of subjects in whom testing was attempted (9154 patients) and the number that completed the tests (7401 patients); eight9–12 14 16 17 24 27 36 studies reported the combined number of attempted and successful tests in patients with ischaemic and haemorrhagic stroke, but not the values for ischaemic stroke alone; and seven studies18 25 26 29 31 34 35 reported cognitive outcomes for 155 patients who only completed some of the assessments. Two studies 12 30 excluded patients with depression (8% of studies, 2% of patients); one study10 measured premorbid IQ using the National Adult Reading Test but did not account for it in the analysis (4% of studies, 3% of patients); and nine studies9–11 15 18 24 26 27 30 interviewed relatives about signs of cognitive decline prior to the index stroke (38% of studies, 19% of patients).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stroke is a major cause of morbidity and mortality around the world, and there is an association between age and the risk of stroke [1]. Ischemic strokes, accounting for 80% of all strokes may be caused due to atherosclerotic disease, embolism, hypercoagulable disorders, and in certain cases, due to undetermined causes [2].…”
Section: Introductionmentioning
confidence: 99%